2021
DOI: 10.1098/rspb.2021.1903
|View full text |Cite
|
Sign up to set email alerts
|

Differential local genetic adaptation to pesticide use in organic and conventional agriculture in an aquatic non-target species

Abstract: Pesticide application is an important stressor to non-target species and can profoundly affect ecosystem functioning. Debates continue on the choice of agricultural practices regarding their environmental impact, and organic farming is considered less detrimental compared to conventional practices. Nevertheless, comparative studies on the impacts of both agricultural approaches on the genetic adaptation of non-target species are lacking. We assessed to what extent organic and conventional agriculture elicit lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 94 publications
0
4
0
1
Order By: Relevance
“…In daphnids, Brans et al (2021) found urban populations of D. magna to be more tolerant to chlorpyrifos than rural populations from the same geographical area (Flanders). In the same region, D. magna populations isolated from ponds located in agricultural areas presented specific pesticide resistance in line with local management practices (either chlorpyrifos or deltamethrin; Almeida et al, 2021). Romero‐Blanco and Alonso (2022) also noted from database and literature review that the sensitivity of aquatic species to contaminants depended strongly on the origin of populations, with either wild or laboratory‐reared populations being the most tolerant, depending on the chemical.…”
Section: Discussionmentioning
confidence: 92%
“…In daphnids, Brans et al (2021) found urban populations of D. magna to be more tolerant to chlorpyrifos than rural populations from the same geographical area (Flanders). In the same region, D. magna populations isolated from ponds located in agricultural areas presented specific pesticide resistance in line with local management practices (either chlorpyrifos or deltamethrin; Almeida et al, 2021). Romero‐Blanco and Alonso (2022) also noted from database and literature review that the sensitivity of aquatic species to contaminants depended strongly on the origin of populations, with either wild or laboratory‐reared populations being the most tolerant, depending on the chemical.…”
Section: Discussionmentioning
confidence: 92%
“…Los resultados obtenidos en el presente estudio concuerdan con los obtenidos por Almeida et al (2021), y Santos et al (2021), quienes hacen referencia a que el sulfato de cobre y el sulfato de aluminio son tóxicos para G. pulex en concentraciones elevadas. La exposición a concentraciones agudas de estos compuestos puede causar la muerte de los individuos en poco tiempo.…”
Section: Exposición a Contaminantesunclassified
“…Four clonal lineages of D. magna were used, originating from small ponds in an agricultural landscape in the province of West-Flanders in Belgium (two from Vleteren: 50 55 0 06.7 00 N, 2 43 0 27.0 00 E and two from De Haan 51 13 0 53.8 00 N, 3 01 0 49.2 00 E; Almeida et al 2021). They were sampled in June 2018 and kept separately in 210 mL glass jars in stock cultures under standardized laboratory conditions (20 AE 1 C, 14 : 10 h light : dark cycle) in aged tap water.…”
Section: Animal Culturementioning
confidence: 99%